2016
DOI: 10.1108/pm-05-2015-0024
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of characteristics affecting employment outcomes and patterns of real estate graduates

Abstract: Purpose – The purpose of this paper is to develop a comprehensive picture of characteristics affecting the employment outcomes and patterns for real estate graduates in Australia. Furthermore, this paper benchmarks the characteristics affecting employment prospects of real estate graduates against those of built environment graduates. Design/methodology/approach – The data used in this paper were collected by the Australian Graduate Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…The study found that Swedish real estate company often typify men as their employees, women are shown as being young and given lesser positions, while both genders are shown in stereotypical positions when presenting companies annual reports. Poon (2016) examined factors affecting employment pattern of real estate and built environment graduates in Australia. Using data collected from the Australian Graduate Survey, and analyzing with the use of descriptive and inferential statistics.…”
Section: Pm 355mentioning
confidence: 99%
See 1 more Smart Citation
“…The study found that Swedish real estate company often typify men as their employees, women are shown as being young and given lesser positions, while both genders are shown in stereotypical positions when presenting companies annual reports. Poon (2016) examined factors affecting employment pattern of real estate and built environment graduates in Australia. Using data collected from the Australian Graduate Survey, and analyzing with the use of descriptive and inferential statistics.…”
Section: Pm 355mentioning
confidence: 99%
“…Factors affecting students' academic performance are diverse and abundant (see for instance Small and Karantonis, 2001;Callanan and McCarthy, 2003;Newell and Acheampong, 2003;Crews 2004;Hermino, 2005;Noble et al, 2006;Kyoshaba 2009;Victor, 2011;Hayat et al, 2013;Ganyaupfu, 2013;Dengra et al, 2013;Adedapo et al, 2015;Kanagi et al, 2015), and it appears that gender variations cannot be dissociated from expected academic output of students in higher institutions of learning. Hence, gender issues with respect to academic achievement are beginning to gain increasing attention across various disciplines and also in workplace performance (see Penner and Paret, 2008;Blanch et al, 2008;Castagnetti and Rosti, 2009;Demirkan and Demirbaş, 2010;Vecchione et al, 2014) and real estate and the built environment is not exempted (Dimovski and Brooks, 2006;Demirkan and Demirbaş, 2010;Dimovski et al, 2016;Poon, 2016). The experience in Nigeria and perhaps other emerging economies appear similar to the observed trends in developed economies, typically having a wide 472 PM 35,5 disparity between males and their female counterparts in the real estate sector and the built environment in general.…”
Section: Introductionmentioning
confidence: 99%
“…Degree levels affect employment patterns of real estate graduates whereas age and gender affected those of built environment graduates. Poon (2016) reported that the employment rates for real estate and built environment graduates who did not speak English at home were low, 11.00 and 16.08 percent respectively. This group of Australian permanent residents is likely to be from families with immigrant backgrounds, and English proficiency affected their chances of securing employment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although Pandey and Pandey (2014) and Pooja (2013) were both writing about the importance of English for employability in India, the situations described are similar in Malaysia as both countries were previously under British rule before their independence. Using the Australian Graduate Survey data from 2010 to 2012, Poon's (2016) analysis revealed that English proficiency has a statistically significant impact on employment outcomes and patterns for the 1,258 real estate and 9,206 built environment graduates. Degree levels affect employment patterns of real estate graduates whereas age and gender affected those of built environment graduates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Overall, the ULI Hines Competition course at Cornell was successful; students strongly agreed that the competition course was a valuable learning experience. Poon (2016) and Poon & Brownlow (2016) shift the emphasis to real estate graduates and employment in Australia. One major finding from the first study was the importance of English proficiency for graduates to get a job within the real estate profession.…”
Section: Literature Reviewmentioning
confidence: 99%